Mobile-Assisted Language Learning (MALL) for vocabulary improvement in A1 Level English students at Universidad Técnica de Cotopaxi - Language Department. - Aguaiza Iza, María Fernanda (2021)
The research project titled “MOBILE-ASSISTED LANGUAGE LEARNING (MALL) FOR VOCABULARY IMPROVEMENT “is based on the application of the Mobile-Assisted Language Learning Approach, as a tool to foster English vocabulary in students from the A1 English Level at Universidad Técnica de Cotopaxi- Language Department. Two groups from the institution were selected. Students who presented poor English level who used their mobile devices in class but not for educational purposes, the project focus on making a research about one of the strategies to involve mobile devices in class in order to enhance English vocabulary in students. 100 students participated in this research, 50 students belong to the control group and the other 50 to the experimental group. The pre-test and post-test were the chosen tools to evaluate English vocabulary proficiency in both groups. The study was carried out under a quali-quantitive method, involving the quasi-experimental design because a pre-test and a post-test were taken. The pre-test was taken at the beginning and the post-test was taken at the end of the proposal application. To evaluate the effectiveness of the proposal the statistical results were analyzed and tabulated thought the t-students test, which was applied to prove that Mobile Assisted Language Learning strategy is useful in order to acquire a foreign language vocabulary proficiency. Regarding this, it is important to implement mobile devices in order to supply students’ needs and help them to enhance English vocabulary proficiency